2013
DOI: 10.1016/j.scriptamat.2012.11.041
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of long-period stacking ordered structures on annealing as-cast Mg85Y9Zn6 alloy ingot observed by synchrotron radiation small-angle scattering

Abstract: Nanostructure of Mg85Y9Zn6 ternary alloy ingot with long-period stacking order structure has been examined by synchrotron radiation small-angle X-ray scattering. The scattering patterns showed sharp reflections corresponding to large domains of 10H, 18R and 14H structures, with in-plane ordering. After annealing at 673 K, the peak intensity of 18R increased, and the diffraction peak corresponding to in-plane ordering sharpened. The domain size of in-plane ordering was much smaller than the domain thickness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 13 publications
3
26
0
Order By: Relevance
“…The microstructure change is similar to the one observed for 1-2 samples. 25) As reported in the previous work on 6-9 and 1-2 alloys, 16,25) the peaks at 3.4 nm ¹1 , 4 nm ¹1 and 4.8 nm ¹1 correspond to compositional modulation of 14H, 18R and 10H stacking orders. The broad peak appearing between 5 nm ¹1 and 6 nm ¹1 is the interference between L1 2 clusters in the segregated layers.…”
Section: ¹1supporting
confidence: 61%
See 2 more Smart Citations
“…The microstructure change is similar to the one observed for 1-2 samples. 25) As reported in the previous work on 6-9 and 1-2 alloys, 16,25) the peaks at 3.4 nm ¹1 , 4 nm ¹1 and 4.8 nm ¹1 correspond to compositional modulation of 14H, 18R and 10H stacking orders. The broad peak appearing between 5 nm ¹1 and 6 nm ¹1 is the interference between L1 2 clusters in the segregated layers.…”
Section: ¹1supporting
confidence: 61%
“…The broad peak appearing between 5 nm ¹1 and 6 nm ¹1 is the interference between L1 2 clusters in the segregated layers. 16,17,24) During heating, the main LPSO periodicity appearing in the sample was 18R for the 3-5 composition, and weak 10H are also observed in the as-cast sample. The 10H peak disappeared at lower temperatures than 18R did, due to relative instability.…”
Section: ¹1mentioning
confidence: 93%
See 1 more Smart Citation
“…Moreover, the dispersion strengthening effect caused by the homogenously distributed MgZn phases enhanced with the increase of the second phase volume fraction [28]. On the other hand, the grain refinement caused by the presence of the Mg-Zn phase and rapid solidification was also beneficial to the improvement of mechanical properties, especially for hexagonal close-packed Mg [29]. Grain boundaries were the effective barriers of grain boundary sliding.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Furthermore, based on Z-contrast scanning transmission electron microscopy and rst principle calculations, Egusa and Abe 15) have proposed a structural model, where Zn and Y atoms form Zn 6 Y 8 L1 2 type clusters around the stacking faults. In addition to the average atomic con gurations of Zn and Y, deviations from the ideal atomic positions of these atoms were discussed with diffraction techniques 15,16) . In these studies, diffuse diffraction spots were observed, which suggests an incomplete in-plane ordering of Zn and Y.…”
Section: Introductionmentioning
confidence: 99%